Evaluation of quality of life in the situative analys of risk factors of generalized parodontal effects in obese young adults - Майбородіна, Діана Дмитрівна; Велика, Наталія Володимирівна; Антоненко, Марина Юріївна (Actual Dentistry, 2019)
Topicality. In young people with obesity, patients with generalized periodontitis, abnormalities in protein, fat and carbohydrate metabolism are detected, which contributes to the early destruction of the complex of periodontal tissues and the rapid loss of teeth. The theoretical models of eating disorders are based on the hypothesis that people with overweight are unable to regulate their emotions, therefore, an appeal to food is an attempt to avoid emotional stress or soften it. Assessing the quality of life of obese patients is necessary for a deeper understanding of the stress factors that affect both the body's health and dental health, including the periodontal tissue. The purpose of the study is to evaluate the quality of life in the situative analys of the risk factors of generalized periodontal effects in obese young adults with disorders of eating behavior. Materials and methods of research. The study was attended by 90 people diagnosed with obesity in the age group of 19 to 35 years, of which 60 people with generalized periodontitis of primary-I degree and 30 persons with generalized chronic catarrhal gingivitis. The control group consisted of 32 practically healthy persons with normal weight, without disturbance of eating behavior, with a clinically intact periodontal disease. To identify types of eating disorders, the DEBQ (Netherlands) eating behavior study methodology was used, questionnaire on quality of life for the GIQLI questionnaire. An antropometric study was conducted for all patients, which included growth measurements, body weight, body mass index (BMI). Results and discussion. In 75.6 % of obese patients (68 people), the quality of life indicators for the GIQLI questionnaire were lower than in the control group (12.5 %, 4 persons). The discrepancy of this indicator in persons with generalized periodontitis and generalized chronic gingivitis was not reliable. Eating disorders occurred during obesity (91.1 % of cases, 82 persons) and in the control group (62.5 % of cases, 20 people). In the Taylor alarm scale, an average level of anxiety with a tendency to high was found in almost 84 obese patients (93.3 %): 18.9±1.82 points (p > 0.05). In 5 patients (5.6 %), a high level of anxiety was detected and one person (1.1 %) was very high. On the Beck scale, in general, the average (M±m) in the obesity group met the sub-depression. Conclusions. The analysis of the data showed that disorders of eating behavior in obese patients with generalized periodontal lesions were found in 90.6% of cases, and in 63.6%, mixed types were detected. Most patients have anxiety depressive disorders and lower quality of life. Key words: obesity, risk factors, disorders of eating behavior, quality of life, periodontitis, gingivitis.